Faculty Service-Learning Students as Home-Visitors: Outcomes of a Lifestyle Modification Program for Vulnerable Families With Residents in Rural Indonesian Communities - Kwok, Stephen Wai Hang; Pang, Phyllis Chui Ping; Chung, Man Hon; Wu, Cynthia Sau Ting (Frontiers in Public Health, 2021)
The risks attribute to chronic diseases, cancer, musculoskeletal discomfort and infectious diseases among Indonesian were found associated with lifestyle behaviors particularly in rural area. The aim of this study was to examine the outcomes of the home visiting lifestyle modification program on improving the health risk behaviors among Indonesian living in rural area. One hundred and sixty Indonesian living in rural hamlets in Yogyakarta region of Indonesia was served in the period of 21st June to 21st July 2019. The first one-hour intervention sessions at home was mainly for identifying the learning needs of diet, exercise, hand hygiene and substance use using the structured assessment tool followed by three home visits in facilitating the behavioral changes. The home-visitors also facilitated the lifestyle planning based on the related affective and cognitive domains of learning. The participants completed the lifestyle assessment tools before the intervention, post intervention on day four to five, and 3-week after intervention in an observed interview. The results showed that the self-reported intake of vegetables, fruits, meat and salt intake, the cooking with less oil, the hand hygiene before eating, number of cigarettes smoked, and the symptoms of muscle stiffness significantly improved after intervention. The lifestyle modification program consisted of the affective and cognitive domains of learning; could lead to the target behavioral changes in the self-reported and observable measures over one month. The findings contributed to the framework of community based health education for health risk reduction and behavioral modification in developing rural communities where health care resources were limited. Further studies with control groups and vigorous objective measures were recommended for its long term impacts. The factors leading to its sustainability of the collaborative care partnership between community residents and faculty resources worth to be explored.